2020
DOI: 10.1111/eci.13356
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of long‐term anticoagulant treatment for the secondary prophylaxis of splanchnic venous thrombosis

Abstract: Background Splanchnic vein thrombosis (SVT) is an uncommon but potentially life‐threatening disease usually related to different underlying clinical conditions. The risk of SVT recurrences is high over time in patients with an underlying permanent prothrombotic condition. Vitamin K antagonists (VKA) represent the mainstay of treatment for SVT. Data about the efficacy and safety of direct oral anticoagulants (DOACs) are reported in the literature for the treatment of acute SVT, but less is known about their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…The second patient, a 38-year-old female without known risk factors and with no evidence of cavernomatosis and esophageal varices, presented a recurrence of portal vein thrombosis 2 years and 5 months after the resolution of the previous one. In literature, several retrospective reports stated the feasibility of DOAC treatment in SVT [ 3 , 4 ], but only one report so far, by Serrao et al [ 5 ], in a cohort of 70 patients, described a safety and efficacy profile not inferior to VKA in long-term prophylaxis, obtaining results similar to ours.
Fig.
…”
supporting
confidence: 80%
“…The second patient, a 38-year-old female without known risk factors and with no evidence of cavernomatosis and esophageal varices, presented a recurrence of portal vein thrombosis 2 years and 5 months after the resolution of the previous one. In literature, several retrospective reports stated the feasibility of DOAC treatment in SVT [ 3 , 4 ], but only one report so far, by Serrao et al [ 5 ], in a cohort of 70 patients, described a safety and efficacy profile not inferior to VKA in long-term prophylaxis, obtaining results similar to ours.
Fig.
…”
supporting
confidence: 80%
“…The overall results of DVT as a disorder of venous physiology are highly dependent on the anatomical position of the thrombosed venous segment [20,28,29]. In recent years, the therapies of acute DVT have become more widespread, but there is still much debate about the priority of treatment in terms of the lowest risk and the best prevention of complications [30]. PTS is still a recurring complication in DVT and leads to significant complications, suffering, and high health costs [17].…”
Section: Discussionmentioning
confidence: 99%
“…12 Riva and Ageno 9 sum ma rize most of the remaining evi dence reporting on the use DOACs in SVT, which con sists mostly of small obser va tional tri als, the major ity ret ro spec tive in nature. Serrao et al 13 describe a recent pro spec tive study of 28 patients with SVT and ongo ing risk fac tors maintained on chronic treatment with war fa rin who were switched to DOACs and com pared out comes to 42 patients remaining on war fa rin. There was no dif fer ence in throm botic events between the groups.…”
Section: Casementioning
confidence: 99%
“…No major bleed ing events occurred in either group, while minor bleed ing did not occur in the DOAC group but was documented in 26% of war fa rin-treated patients (P = .09). 13 In the larg est of the ret ro spec tive tri als, Naymagon et al 14 in Blood Advances reported on 93 patients with noncirrhotic portal vein treated with apixaban (n = 20), rivaroxaban (n = 65), and dabigatran (n = 8) com pared with low molec u lar weight hep a rin (LMWH) (n = 70) and war fa rin (n = 108). 14 Seventy-three per cent of patients had predisposing fac tors for PVT.…”
Section: Casementioning
confidence: 99%